Edible Coatings to Reduce Postharvest Loss of Harumanis Mango (Mangifera indica L.) - Winda Amilia; Andrew Setiawan Rusdianto; Sayidati Zulaikhah (Newinera Publisher, 2020)
Harumanis is type of mango in Indonesia that meets the needs of export or local markets. Harumanis mango have not been able to fully boost the rate of export of this Indonesian fresh fruit due to poor postharvest technology. This condition has an adverse impact as it increases postharvest loss. Thus, in these conditions there must be postharvet handling of harumanis mango, one of which is edible coating made from chitosan with the addition of starch. The difference in the value of amylose and amylopectin from starch resulted in differen results. The aim of this research was to determine the effect of addition of starch types in chitosan edible coating on the postharvest loss of harumanis mango based onthe physico-chemical tests. The experiment used completely randomized design with two factor. The parameters observed were physical test including weight loss, texture, and color. Chemical test including respiration rate, vitamin C, and total soluble solids. The result showed that the addition of starch on chitosan edible coating significantly affected postharvest loss to the results of physical and chemical tests. The best treatment was the addition of starh to edible coating with chitosan because it can provide physical and chemical defense during storage at room temperature.